IMPROVING VOCABULARY IN STUDENTS’ SPEAKING ABILITY BY USING MODELLING THE WAY - Hafid, Syahrul Sidan; Sholichah, Norma Ita (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Vocabulary is all the words belonging to a language owned by a person or also owned by a speaker. The more vocabulary you have, the more skilled a person's patterns are in writing, such as narrative writing. To communicate information or roles to its readers, it needs a lot of words. In this research, the researcher applied Modeling The Way to solve the problems that were faced by the students. This research was conducted in order to Improving Vocabulary in Students’ Speaking Ability by Using Modelling The Way for the Fourth Grade at MI Miftahul Huda Prangas. In conducting this research, the researcher used Classroom Action Research (CAR) as the method of research. The researcher conducted this research in two cycles. First cycle is guiding consisted of two meetings and second cycle is implementing consisted of one meeting. The researcher used modeling The Way to make pleasant atmosphere during teaching and learning process of vocabulary, and more importantly to improve vocabulary in students’ speaking ability. The subject of this research was the students of fourth grader students in MI Miftahul Huda Prangas. The instruments to collect the data were observation checklist, and vocabulary test. The result of this research showed that by using Modeling The Way Technique in teaching vocabulary, especially in daily activities. The researcher could improve vocabulary of the students. Their responses showed that they were interested to learn vocabulary subject because they felt easier to memorizing vocabulary, understand and got new vocabulary using Modeling The Way Technique. Based on the result of cycle 1 the average of their score is 74. The result of cycle 2, the average of their score is 81